Oxidative Stress: An Effective Prognostic Tool for an Early Detection of Cardiovascular Disease in Menopausal Women - Jyot Amrita; Mridula Mahajan; A. J. S. Bhanwer; Gurinder Mohan (Biochemistry Research International)
Background. Menopause, a form of reproductive aging, is marked by many hormonal variations which cause imbalance in the oxidative processes resulting in onset of endothelial dysfunction leading to cardiovascular disease (CVD). We aimed to analyze the effect of oxidative stress in an early detection of CVD in all menopausal women both normolipidemic and hyperlipidemic. Methods and Results. Study included 523 menopausal women (265 CVD and 258 non-CVD). They were screened for lipid profile, serum malondialdehyde (MDA), serum LDL carbonyl protein, and serum superoxide dismutase (SOD). Pearson’s correlation was observed between MDA and atherogenic index of plasma (AIP) in both normolipidemic (r=0.650; p<0.001) and hyperlipidemic (r=0.207; p<0.01) CVD group as compared to non-CVD menopausal women. Significant correlation was also observed between LDL carbonyl content and AIP in normolipidemic (r=0.650; p<0.001) and hyperlipidemic (r=0.248; p<0.01) CVD menopausal women as compared to non-CVD ones. Conclusion. Strong correlation between atherogenic index of plasma and oxidative stress in CVD menopausal women reveals oxidative stress as an effective prognostic tool for an early detection of cardiovascular risk.